Polymer gel dosimeter based on itaconic acid. (November 2015) - Mattea, Facundo; Chacón, David; Vedelago, José; Valente, Mauro; Strumia, Miriam C.
Abstract: A new polymeric dosimeter based on itaconic acid and N, N'-methylenebisacrylamide was studied. The preparation method, compositions of monomer and crosslinking agent and the presence of oxygen in the dosimetric system were analyzed. The resulting materials were irradiated with an X-ray tube at 158 cGy/min, 226 cGy min and 298 cGy/min with doses up to 1000 Gy. The dosimeters presented a linear response in the dose range 75–1000 Gy, sensitivities of 0.037 1/Gy at 298 cGy/min and an increase in the sensitivity with lower dose rates. One of the most relevant outcomes in this study was obtaining different monomer to crosslinker inclusion in the formed gel for the dosimeters where oxygen was purged during the preparation method. This effect has not been reported in other typical dosimeters and could be attributed to the large differences in the reactivity among these species. Highlights: A novel polymer gel dosimeters based on itaconic acid is presented and characterized. The typical linear trend of the dose behavior in a specific dose range was found. Different gel structures were formed when oxygen and an antioxidant were present. Absorbed dose is univocally correlated with optic absorbance and Raman spectroscopy. Itaconic acid appears as a reliable radiation dosimeter that may be further improved.